(untitled) - Walde, David (London, 1973)
The Russo-Japanese of 1904-5 was a European conflict fought by proxy in Korea, Manchuria and the South China Sea. Its origins lay in a Europe stalemated by military alliances. The Trans-Siberian Railway gave the traditional dimension. Russia now had access to the Pacific; her imperial presence in Asia threatened astablished British interests in the Far East.
Keywords: Russo-japanese war; 1904-1905